Neuromuscular but not technical performance is affected by time-of-day in semiprofessional, female basketball players - Gaos, S.; Sánchez-Jorge, S.; Muñoz, A.; Vicente-Campos, D.; Acebes-Sánchez, J.; Esquius, L.; Scanlan, A. T.; López-Samanes, Á. (Research Quarterly for Exercise and Sport, 2024)
Purpose The aim of this study was to determine whether variations in technical and neuromuscular performance occur across different times of the day in basketball players.